1995
DOI: 10.1093/mutage/10.6.543
|View full text |Cite
|
Sign up to set email alerts
|

Preferential repair in Saccharomyces cerevisiae rad mustants after induction of interstrand cross-links by 8-methoxypsoralen plus UVA

Abstract: The gene specific induction and the incision step of the removal of 8-methoxypsoralen (8-MOP) plus UVA-induced interstrand cross-links (ICL) was measured in repair mutants of Saccharomyces cerevisiae. Events were examined at the MAT alpha and HML alpha loci in mutants deficient in the repair of ICL, namely rad1, rad2 delta, rad52, pso2 and the rad16 mutant which is impaired in the removal of UV-induced pyrimidine dimers from the silent HML alpha locus. Previously, we observed in a wild-type strain (K107) prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…The sensitivity of snm1 mutants to all ICL agents tested suggests that Snm1 is involved in an ICL agent-independent step and therefore probably after the formation of ICLs (6,25,49). This notion is consistent with the fact that snm1 mutants are capable of creating DSBs after treatment with 8-methoxypsoralen plus UVA light, in contrast to NER mutants, which are not able to incise the DNA near the ICL (40,42). snm1 mutants are, however, epistatic with NER mutants, suggesting that they play a role in this repair pathway (24,51).…”
Section: Discussionsupporting
confidence: 70%
“…The sensitivity of snm1 mutants to all ICL agents tested suggests that Snm1 is involved in an ICL agent-independent step and therefore probably after the formation of ICLs (6,25,49). This notion is consistent with the fact that snm1 mutants are capable of creating DSBs after treatment with 8-methoxypsoralen plus UVA light, in contrast to NER mutants, which are not able to incise the DNA near the ICL (40,42). snm1 mutants are, however, epistatic with NER mutants, suggesting that they play a role in this repair pathway (24,51).…”
Section: Discussionsupporting
confidence: 70%
“…It was also observed that the conserved domain within the Snm1 homologs represents a metallo-␤-lactamase fold, implying that these proteins contain a hydrolase activity that has been reported to encode a nuclease activity that may be involved in processing the ends of double-strand breaks (31). Since studies with yeast snm1 mutants have shown that they are not deficient in the initial incision events that occur at crosslinks but are defective in a later step required for the restoration of high-molecularweight DNA from fragmented DNA (24,27), the yeast homolog may be involved in the recognition and/or processing of double-strand breaks that occur as intermediates during interstrand crosslink repair.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular analysis of snm1 mutants treated with either nitrogen mustard or psoralen plus UVA showed that incision near the sites of interstrand crosslinks proceeded normally; however, a late step in interstrand crosslink repair that is required for restoration of high-molecular-weight DNA appeared to be defective (24,27). Molecular cloning of the yeast SNM1 gene showed that it encoded a novel 76-kDa protein with a nuclear localization signal and one putative zinc finger motif (14,38).…”
mentioning
confidence: 99%
“…Outside the SNM1 domain, the sequences of the yeast and human proteins are different. The function of yeast Snm1 remains largely unresolved, although several studies have indicated that it is involved in repairing double-strand breaks (DSBs) resulting from processing of interstrand cross-links (31,35,40). Artemis was originally identified molecularly as deficient in a human radiosensitive severe combined immunodeficiency syndrome (RS-SCID) (41), which is characterized by a defect in V(D)J recombination resulting in premature arrest of both B-and T-cell maturation.…”
mentioning
confidence: 99%